The Studies of Prognostic Factors and the Genetic Polymorphism of Methylenetetrahydrofolate Reductase C667T in Thymic Epithelial Tumors - Yan, Miaolong; Wu, Jiayuan; Xue, Min; Mo, Juanfen; Zheng, Li; Zhang, Jun; Gao, Zhenzhen; Bao, Yi (Frontiers in Oncology, 2022)
Objective: To describe the clinical features of a cohort of patients with thymic epithelial tumours (TETs) and to analyze their prognostic factors. In particular, we investigated the correlation between the genetic polymorphism of methylenetetrahydrofolate reductase (MTHFR) C667T and the incidence of TETs was investigated. Methods: Pathological records were reviewed from the database of the Second Affiliated Hospital of Jiaxing University, from January 2010 to December 2020, and 84 patients with TETs were recruited for this study. Univariate and multivariate analyses were performed to determine the prognostic factors. The genetic polymorphism of MTHFR C667T was examined in the patients with TETs and in a group of healthy individuals. The correlation between MTHFR transcriptional levels and methylation was analysed using The Cancer Genome Atlas (TCGA) thymoma dataset from the cBioPortal platform. Results: Kaplan-Meier univariate survival analysis showed that sex, age, maximum tumour diameter, surgery, chemotherapy, radiotherapy, WHO histological classification, Masaoka-Koga stage, and 8th UICC/AJCC TNM staging, were statistically significantly correlated with the prognosis of patients with TETs. Masaoka-Koga stage and 8th UICC/AJCC TNM staging were strongly correlated with each other in this study (r=0.925, P<0.001). Cox multivariate survival analysis showed that maximum tumour diameter, Masaoka-Koga stage, and 8th UICC/AJCC TNM staging were independent prognostic factors affecting the overall survival (OS) of patients with TETs (P<0.05). The MTHFR C667T genotype (χ2=7.987, P=0.018) and allele distribution (χ2=5.750, P=0.016) were significantly different between the patients and healthy controls. CT Heterozygous and TT homozygous genotypes at this MTHFR polymorphrism significantly increased the risk of TETs (odds ratio [OR] =4.721, P=0.008). Kaplan-Meier univariate survival analysis showed that there was no correlation between different genotypes and the prognosis of TETs (CC versus CT + TT, χ2=0.003, P=0.959). Finally, a negative correlation between the transcriptional and methylation levels of MTHFR was observed in the TCGA thymoma dataset (r=-0.24, P=0.010). Conclusions: The Masaoka-Koga stage, 8th UICC/AJCC TNM staging, and the maximum tumour diameter were independent prognostic factors for TETs. Reduced methylation levels of MTHFR and particular polymorphic variants may contribute to the susceptibility to developing TETs.